2018
DOI: 10.3389/fneur.2018.00074
|View full text |Cite
|
Sign up to set email alerts
|

A Score for Risk of Thrombolysis-Associated Hemorrhage Including Pretreatment with Statins

Abstract: BackgroundSymptomatic intracranial hemorrhage (sICH) after intravenous thrombolysis with recombinant tissue-plasminogen activator (rt-PA) for acute ischemic stroke is associated with a poor functional outcome. We aimed to develop a score assessing risk of sICH including novel putative predictors—namely, pretreatment with statins and severe renal impairment.MethodsWe analyzed our local cohort (Berlin) of patients receiving rt-PA for acute ischemic stroke between 2006 and 2016. Outcome was sICH according to ECAS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 32 publications
(37 reference statements)
1
18
0
Order By: Relevance
“…The characteristics of the included studies are presented in Table 1 . Overall, this meta-analysis included 12 prospective cohort studies ( 10 , 11 , 13 , 14 , 16 18 , 20 23 , 27 ), five retrospective cohort studies ( 9 , 12 , 15 , 19 , 26 ), and three post-hoc analyses of RCTs ( 24 , 25 , 28 ), with a total of 20,752 AIS patients who were treated with IVT. The mean ages of the included patients varied between 63 and 75 years, and the baseline NIHSS varied from 7 to 17.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of the included studies are presented in Table 1 . Overall, this meta-analysis included 12 prospective cohort studies ( 10 , 11 , 13 , 14 , 16 18 , 20 23 , 27 ), five retrospective cohort studies ( 9 , 12 , 15 , 19 , 26 ), and three post-hoc analyses of RCTs ( 24 , 25 , 28 ), with a total of 20,752 AIS patients who were treated with IVT. The mean ages of the included patients varied between 63 and 75 years, and the baseline NIHSS varied from 7 to 17.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the premorbid use of statin was associated with an increased risk of SIH in AIS after IVT [16 studies ( 10 14 , 16 18 , 20 25 , 27 , 28 ), OR: 1.48, 95% CI: 1.12–1.95, p = 0.006, I 2 = 60%; Figure 4 ]. Consistent results were retrieved in subgroup analyses according to study design ( Figure 4A ) or adjustment of LDL-C at baseline ( Figure 4B ).…”
Section: Resultsmentioning
confidence: 99%
“…7 Despite the beneficial effects, some studies have shown that statins decrease platelet aggregation and thrombogenesis 8 , which may be related to symptomatic intracranial hemorrhages (sICH) and exacerbate unfavorable outcomes. 9 Some studies have reported that prior statin use (PSU) was associated with improved functional outcomes 10,11,14,17,18 , but these findings have not been consistently replicated. 12,13,15,16,19,20 Some studies have shown that statin use before thrombolysis is associated with adverse outcomes such as increased mortality and sICH.…”
Section: Introductionmentioning
confidence: 99%
“…Prior statin use has been associated to increased risk of SICH, but it did not have any impact on outcomes according to cases series of 311 and 182 patients treated[3637] and three European registries totaling 2482 patients. [373839] In another registry of 606 patients, the risk of SICH was not increased (OR: 0.57; 95% confidence interval [CI]: 0.22–1.49)[40] and in a meta-analysis of 11 studies and 6438 patients, the statin use neither increased the risk of SICH nor was associated with more favorable outcomes. [40]…”
Section: Introductionmentioning
confidence: 99%